Peran Sektor UMKM dalam Menekan Inflasi dan Menyerap Tenaga Kerja di Surabaya - Naysilla Chairani; Nisrina Zasmin; Rahman Raisuli; Akhmad Rasyid Rosidi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays a pivotal role in Indonesia's economy, particularly in cities like Surabaya. This article aims to analyze the contribution of MSMEs in curbing inflation and absorbing labor in Surabaya. Using a qualitative descriptive method, this study reviews existing literature and data from various sources. The findings indicate that MSMEs significantly absorb labor, thereby reducing unemployment and increasing community income, which in turn helps control inflation. However, challenges such as limited access to capital and technology remain. Strengthening MSMEs is crucial for economic stability and employment in Surabaya.